Facilitating public interest environmental litigation through locus standi: a comparative analysis of South Africa and Germany - Brennecke, Nicolas (Institute of Marine and Environmental Law, 2017)
The purpose of this dissertation is to undertake a critical and comparative review of South Africa and Germany's legislation and jurisprudence of relevance to facilitating public interest environmental litigation through the liberalisation of locus standi requirements. The dissertation presents the theoretical framework and explains the origin of public interest litigation and defines the term and its growing impetus in the environmental context. It further examines the term locus standi and the inherent link of public interest litigation with the liberalisation of locus standi requirements. Furthermore, it presents the theory behind the key elements which kind of interest is sufficient to found locus standi, which persons/entities are accorded locus standi, and which procedural issues such as environmental costs relate to locus standi. Regarding South Africa, the dissertation demonstrates how the traditionally restrictive approach regarding locus standi entirely changed with the adoptions of the 1994 Interim and 1996 Final Constitutions and the 1998 NEMA, which have broadly enhanced plaintiffs litigating in the public interest in environmental matters. Apart from the pre-Constitutional context and the current legal framework, it evaluates the new approach with reference to court decisions and how these have addressed the aforementioned key elements influencing locus standi. Regarding Germany, the dissertation examines how its legal system, historically always focused on the protection of individual rights, has been extensively influenced by both international law such as the Aarhus Convention and European Union (EU) law, which have both promoted wider access to courts in environmental litigation. This part also examines both the legal framework and court decisions and the issue of how these court decisions have dealt with the three key elements. While the dissertation concludes that South Africa has liberalised its locus standi requirements in a more consistent manner, it argues that the liberalisation of locus standi requirements has not opened the often-feared floodgates in both jurisdictions. The dissertation presents the specific lessons Germany can learn from South Africa to facilitate public interest environmental litigation. On the one hand, it can learn from South Africa's clear and ambitious legal framework and from its mostly correspondingly progressive court decisions as well, while on the other hand some court decisions do not follow suit. Furthermore, the dissertation also illustrates the significant obstacles to implementing these lessons in Germany. Regarding the range of plaintiffs that are accorded locus standi, it argues that neither international nor EU law have demanded Germany to implement such a wide extension of locus standi requirements as in South Africa. Concerning the kind of interest plaintiffs must show, Germany is under no obligation to give up its focus on the protection of individual rights entirely either. Regarding this issue and the issue of environmental costs, the dissertation concludes that in Germany there is still urgent need for reforms such as properly implementing the Aarhus Convention, though.